Development of a new index for methane drainageability of a coal seam using the fuzzy rock engineering system (Rudarsko-geološko-naftni zbornik, 2019)
Coal seam gas is one of the most significant energy resources in unconventional gas fields. The identification of influenc- ing parameters and methane drainage assessment are, thus, a prime geotechnical focus for all potential methane drain- age projects. In methane drainage operations of coal seams, many factors, such as natural factors and operational factors affect the drainage efficiency. In this paper, a new coal seam methane drainageability index (CMDI) is introduced for pre-drainage techniques in a working mine. In this approach, seventeen parameters are considered as the main factors affecting the methane drainage form coal seam, and the interaction matrix based on the fuzzy rock engineering system (FRES), which analyzes the interrelationship between the parameters affecting methane drainage activities, are used to study coal seam methane drainageability. Since the value of interaction in the RES method is not unique, the fuzzy sys- tem is used to minimize subjectivity of the weights which are computed in the RES method. The Tabas coal mine (Iran) was selected as a case study and the proposed index was used to rank the C1 seam in this mine. It was observed that the methane drainageability index could suitably predict the potential of the methane drainage of coal seam. The newly proposed index can be used as a basis for decision-making when uncertainties about the evaluation of the parameters affect the methane drainage of a coal seam and reduce the risk of methane drainage projects.